Parental Modeling as Predictor of Filial Obligation in Young Adults - Fatima Khan, Farhat Jami, Ruhi Khalid (Pakistan Journal of Psychology, 2017)
Filial obligation plays a vital role in family functioning and interaction with parents. The role of parental modeling as a factor contributing to filial obligation was explored in 200 men and women with an age range between 25 to 35 years with mean age of 28.27(± SD 2.38). It was hypothesized that parental modeling would predict filial obligation (i.e. Contact and Family Ritual, Conflict Avoidance, Assistance, Self-Sufficient and Personal Sharing). In addition, the gender differences on Filial Obligation were also examined. The Self-developed Parental Modeling Questionnaire (PMQ) and Felt Obligation Measure (FOM; Stein, 1992) along with a Structured Interview Schedule were used. The Linear Regression analysis and t-test were employed for statistical analysis of data. The results indicated that parental modeling is a significant predictor of filial obligation in young adults. Further, gender differences were observed on four domains of filial obligation except for Self-Sufficient sub-domain. The implications of results for healthy parent child interaction are discussed.